The sequence of transformation is a reflection across the x-axis, followed by horizontal shift to the right by 2 units, and vertical shift up by 6 units
The vertices of triangle ABC are given as:
[tex]A = (1,9)[/tex]
[tex]B = (3,12)[/tex]
[tex]C =(4,4)[/tex]
The vertices of triangle A"B"C" are given as:
[tex]A" = (3,-3)[/tex]
[tex]B" = (5,-6)[/tex]
[tex]C" =(6,2)[/tex]
Start by reflecting the coordinates of triangle ABC across the x-axis.
The rule of this transformation is:
[tex](x,y) \to (x,-y)[/tex]
So, we have:
[tex]A' =(1,-9)[/tex]
[tex]B' =(3,-12)[/tex]
[tex]C' =(4,-4)[/tex]
Next, shift triangle A'B'C' 2 units right and 6 units up
The rule of this transformation is:
[tex](x,y) \to (x+2,y+6)[/tex]
So, we have:
[tex]A" = (3,-3)[/tex]
[tex]B" = (5,-6)[/tex]
[tex]C" =(6,2)[/tex]
Hence, the sequence of transformation is a reflection across the x-axis, followed by horizontal shift to the right by 2 units, and vertical shift up by 6 units
Read more about transformation at:
https://brainly.com/question/1448141